Analisis Faktor-Faktor Determinasi Auditor terhadap Penerbitan Opini Audit Going Concern - Ramadhani, Salsabila; Mulyani, Erly (Jurnal Eksplorasi Akuntansi, 2025)
This research was conducted to determine the effect of company size, KAP reputation, profitability, audit report lag, liquidity, and leverage on the issuance of going concern audit opinions. This research is quantitative research. The data sources used are secondary data in the form of annual financial reports and independent audit reports. The population used in this study was consumer cyclicals sector companies listed on the Indonesia Stock Exchange from 2019 to 2023. Sampling was carried out using the purposive sampling technique and obtained 54 out of 165 observation data. The results of this study indicate that company size, KAP reputation, profitability, audit report lag, and liquidity do not affect going concern audit opinions. While leverage has a positive effect on going concern opinions.